Money Laundering in Terrorism Financing: Transnational Crime Context - Banjarani, Desia Rakhma; Putri, Taufani Yunithia; Andreas, Ricco; Ervita, Mona; Tahirah, Dhafina Marsyah; Anditya, Ariesta Wibisono (Kertha Patrika, 2026)
Even though currently many have set various policies to prevent and eradicate money laundering and terrorism, in reality these two criminal acts still occur frequently. This research wants to take a deeper look at the crime of money laundering in terrorism financing based on a review of transnational crime. The aims of this research, namely to analyze money laundering and terrorism financing involved in transnational crime and to identify money laundering law enforced in terrorism financing. This research is normative legal research that uses a statutory approach. The purpose of this research is to find intersection between money laundering and terrorism financing involved in transnational crime and to analyses money laundering law enforced in terrorism financing. The result of this research is the intersection between money laundering and terrorism lies in their mutual violation of law and potential to cause widespread harm is an act that violates the law and harms many people. Terrorism and other criminal acts related to terrorism are a form of transnational organized crime, because they involve complex international networks. Various efforts to eradicate money laundering, especially at the international level related to terrorism, were carried out by member countries of the Organization for Economic Co-operation and Development (OECD).